2014
DOI: 10.2298/jsc121216059l
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of lansoprazole at a multiwalled carbon nanotubes-ionic liquid modified glassy carbon electrode and its electrochemical determination

Abstract: The electrochemical behavior of lansoprazole (LNS) was investigated at a glassy carbon electrode (GCE) and the GCE modified by a gel containing multiwalled carbon nanotubes (MWCNTs) and a room-temperature ionic liquid (RTIL) of 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF 6 ) in 0.10 M phosphate buffer solution of pH 6.8. It was found that an irreversible anodic oxidation peak with an E pa of 1.060 V SCE appeared at the MWCNTs--RTIL/GCE. Under the optimized experimental conditions a linear calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In order to understand the possible responsible group in the oxidation of MPB, CV curves were obtained in different supporting electrolytes, which were solutions of 0.5 M H 2 SO 4 , pH 3.0 PB, and pH 3.5 AcB, and both MPB and model compounds showed similar behavior. According to the results obtained, it was concluded that the possible oxidation of MPB occurred through the nitrogen atom of the benzimidazole group forming a radical cation in acidic media, similar to that suggested in other compounds belonging to the benzimidazole family [21,31–34] …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…In order to understand the possible responsible group in the oxidation of MPB, CV curves were obtained in different supporting electrolytes, which were solutions of 0.5 M H 2 SO 4 , pH 3.0 PB, and pH 3.5 AcB, and both MPB and model compounds showed similar behavior. According to the results obtained, it was concluded that the possible oxidation of MPB occurred through the nitrogen atom of the benzimidazole group forming a radical cation in acidic media, similar to that suggested in other compounds belonging to the benzimidazole family [21,31–34] …”
Section: Resultssupporting
confidence: 71%
“…According to the results obtained, it was concluded that the possible oxidation of MPB occurred through the nitrogen atom of the benzimidazole group forming a radical cation in acidic media, similar to that suggested in other compounds belonging to the benzimidazole family. [21,[31][32][33][34]…”
Section: Oxidation Of Mpbmentioning
confidence: 99%
“…Wu et al successfully created a new multi-walled carbon nanotube (MT) based therapeutic delivery system by agent hydroxy camptothecin (HCPT) of tethering anticancer onto the surface of MTs [26]. Li-Hong et al [27] investigated electrochemical kinetics behavior and quantitative determination of Lansoprazole (LNS) by several electrochemical methods using an application of MTs.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28]30 Voltammetric techniques such as square-wave adsorptive stripping voltammetry, differential pulse voltammetry, and anodic voltammetry have also been used for assay of lansoprazole. 29,31,32 However, analytical methods based on HPLC, HPTLC, spectrophotometry, capillary electrophoresis, and flow analysis are either associated with multiple sample preparation steps and longer analysis time or very costly. The electrochemical methods using a mercury electrode for reduction of lansoprazole may be associated with the environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, electroanalytical methods have been developed for estimation of lansoprazole. The polarographic behavior of lansoprazole was investigated at the dropping mercury electrode which has been exploited to develop methods for its assay in dosage forms. , Voltammetric techniques such as square-wave adsorptive stripping voltammetry, differential pulse voltammetry, and anodic voltammetry have also been used for assay of lansoprazole. ,, However, analytical methods based on HPLC, HPTLC, spectrophotometry, capillary electrophoresis, and flow analysis are either associated with multiple sample preparation steps and longer analysis time or very costly. The electrochemical methods using a mercury electrode for reduction of lansoprazole may be associated with the environmental pollution.…”
Section: Introductionmentioning
confidence: 99%